2004
DOI: 10.14411/eje.2004.070
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of females and differentiation between populations of Epirrita autumnata (Lepidoptera: Geometridae) inferred from variation in mitochondrial DNA

Abstract: Abstract. Analysis of the mitochondrial DNA (mtDNA) control region (CR) was used to examine the dispersal of females of a geometrid moth, Epirrita autumnata, in Fennoscandia. A 542-bp-portion of the CR of 200 individuals from four northern and four southern localities was sequenced. The mtDNA CR of E. autumnata contains a substantial amount of variation as a total of 108 mtDNA haplotypes were observed. Between the northern and the southern localities (~1100 km), there was a moderate level of genetic differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…They found less variation in northern‐ compared with southern populations, which they argue might be a result of the northern moths' cyclic population dynamics (Futuyma ; Snäll et al. ). Their results also revealed moderate levels of divergence between the northern and southern populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found less variation in northern‐ compared with southern populations, which they argue might be a result of the northern moths' cyclic population dynamics (Futuyma ; Snäll et al. ). Their results also revealed moderate levels of divergence between the northern and southern populations.…”
Section: Discussionmentioning
confidence: 99%
“…Snäll et al. () analyzed the mtDNA control region investigating the dispersal of E. autumnata females and differentiation between northern‐ (Norwegian samples) and southern (Finnish samples) E. autumnata populations. They found less variation in northern‐ compared with southern populations, which they argue might be a result of the northern moths' cyclic population dynamics (Futuyma ; Snäll et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Du Merle (1999) and Horstmann (1984) indicate a high dispersal activity in line with our laboratory observations for males, where males showed a much higher activity than females (data not shown). A recent study on gene flow in a geometrid species (Epirrita autumnata) yielded similar results (Snä ll et al, 2004). Snä ll et al (2004) observed that the females of E. autumnata are weak flyers and expected genetic differences already in a small area (up to 19 km 2 ) using mitochondrial markers, but they found no genetic differences in a small area and only a moderate amount of genetic differences in a large area of about 1000 km 2 .…”
Section: Genetic Differences In T Viridanamentioning
confidence: 68%
“…A recent study on gene flow in a geometrid species (Epirrita autumnata) yielded similar results (Snä ll et al, 2004). Snä ll et al (2004) observed that the females of E. autumnata are weak flyers and expected genetic differences already in a small area (up to 19 km 2 ) using mitochondrial markers, but they found no genetic differences in a small area and only a moderate amount of genetic differences in a large area of about 1000 km 2 . These results were attributed to high gene flow, either because the adult females had a high rate of dispersal or because the historical gene flow was high.…”
Section: Genetic Differences In T Viridanamentioning
confidence: 68%